Mad, bad and sad: A history of women and the mind doctors - Appignanesi, Lisa (W.W. Norton & Company, 2009)
De la dépression subie par Virginia Woolf et Sylvia Plath à l'angoisse mentale et aux dépendances des beautés emblématiques Zelda Fitzgerald et Marilyn Monroe. De Théroigne de Méricourt, Furie de la Gironde, qui descendit des triomphes sanglants de la Révolution française à la folie indomptable dans l'asile de La Salpêtrière, à Mary Lamb, sœur de Charles, qui, en pleine dépression nerveuse, se retourna contre sa mère avec un couteau de cuisine. De Freud et Jung à Lacan et les nouvelles thérapies centrées sur les femmes. C'est l'histoire de la façon dont nous avons compris les états d'esprit extrêmes au cours des deux cents dernières années et comment nous les concevons aujourd'hui, alors que de plus en plus de notre vie intérieure et de nos émotions sont devenues une affaire de médecins et de thérapeutes. Voici aussi l'histoire des professions qui se sont développées pour offrir des soins, comment, au fil des ans, les symptômes et les diagnostics se sont développés ensemble pour créer des modes dans la maladie et comment les traitements ont réussi ou parfois échoué, même lorsque les soignants étaient également des femmes. "Mad, Bad and Sad" nous emmène dans un voyage fascinant à travers l'esprit humain fragile et extraordinaire.
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; cours; discipline; fem1000; femmes*; histoire; histoire et politique; premier cycle; psychanalyse; périodes historiques; santé; santé mentale; sciences humaines; thématiques

A call to incorporate a reproductive justice agenda into reproductive health clinical practice and policy - Gilliam, Melissa L.; Neustadt, Amy; Gordon, Rivka (Contraception, 2009)
Keywords: approches et analyses; contraception; discipline; droits des femmes*; intersectionnalité; inégalités; justice reproductive; justice sociale; médecine; ressource en ligne; santé; santé des femmes*; sciences; sciences humaines; sexologie; systèmes d'oppressions; thématiques

From gender bias to gender awareness in medical education - Verdonk, Petra; Benschop, Yvonne W. M.; de Haes, Hanneke C. J. M.; Lagro-Janssen, Toine L. M. (Advances in Health Sciences Education, 2009)
Gender is an essential determinant of health and illness. Gender awareness in doctors contributes to equity and equality in health and aims towards better health for men and women. Nevertheless, gender has largely been ignored in medicine. First, it is stated that medicine was ‘gender blind’ by not considering gender whenever relevant. Secondly, medicine is said to be ‘male biased’ because the largest body of knowledge on health and illness is about men and their health. Thirdly, gender role ideology negatively influences treatment and health outcomes. Finally, gender inequality has been overlooked as a determinant of health and illness. The uptake of gender issues in medical education brings about specific challenges for several reasons. For instance, the political-ideological connotations of gender issues create resistance especially in traditionalists in medical schools. Secondly, it is necessary to clarify which gender issues must be integrated in which domains. Also, some are interdisciplinary issues and as such more difficult to integrate. Finally, schools need assistance with implementation. The integration of psychosocial issues along with biomedical ones in clinical cases, the dissemination of literature and education material, staff education, and efforts towards structural embedding of gender in curricula are determining factors for successful implementation. Gender equity is not a spontaneous process. Medical education provides specific opportunities that may contribute to transformation for medical schools educate future doctors for future patients in future settings. Consequently, future benefits legitimize the integration of gender as a qualitative investment in medical education.
Keywords: approches et analyses; discipline; europe; formation des médecins; médecine; pays-bas; projet charge mentale; rapports sociaux de sexe; régions géographiques; santé; sciences; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; éducation